Competencies of Engineers in Industry 4.0 (Research, Society and Development, 2022)
Industry 4.0 has gained prominence in the last decade, becoming fundamental in manufacturing environments; this situation imposed changes in the skills required of employees working in the institutions. The article intends to understand what skills engineering professionals must have to work in this recent production methodology. The work was developed through a systematic literature review, using the Scopus database as a search engine, and had as strings expressions related to industry 4.0, engineering skills and engineering training. IRAMUTEQ software was also used to support research interpretations. The results showed a set of skills necessary for engineers to work in Industry 4.0: personal, social, action, methodological and technical skills. Furthermore, using the IRAMUTEQ software, it was possible to create word clouds using research articles; this cloud highlighted the expressions: Industry, Competence, Learning, Technology, Teaching and Research., concluding that within the theme, these aspects are of fundamental importance.